2011
DOI: 10.1016/j.ygyno.2010.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for recurrence of ovarian borderline tumors

Abstract: Objective The objective of this study was to identify clinicopathologic features that are associated with an increased risk of recurrence for borderline ovarian tumors (BOT). Methods We performed a retrospective review of all patients treated for BOT at our institution from 1979–2008. Progression-free survival (PFS) was defined as the time of diagnosis to time of recurrence/death or last follow-up. The Kaplan-Meier method was used to calculate the PFS rate and Wilcoxon Gehan test was performed to identify pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
61
3
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 33 publications
6
61
3
2
Order By: Relevance
“…In a study on the risk factors for recurrence in BOT, it was shown that higher serum levels of CA 125 and advanced stages of BOT were associated with higher recurrence rate (19). In the current study, there was a marginal significant difference in the stage of disease, between the 2 groups.…”
Section: Discussioncontrasting
confidence: 45%
“…In a study on the risk factors for recurrence in BOT, it was shown that higher serum levels of CA 125 and advanced stages of BOT were associated with higher recurrence rate (19). In the current study, there was a marginal significant difference in the stage of disease, between the 2 groups.…”
Section: Discussioncontrasting
confidence: 45%
“…While lymphadenectomy is part of surgical staging in ovarian cancer, it has not been shown to be prognostically significant in BOT [15]. In many study, lymph node dissection or nodal involvement has no impact on recurrence or survival [13,16,17]. This finding provides further evidence that routine lymphadenectomy may not be necessary with BOT.…”
Section: Resultsmentioning
confidence: 97%
“…These patients were managed with I, conservative treatment is strongly recommended [12]. In the study of Shih et al [13] risk of recurrence was higher in patients who undergo conservative surgery compared with those patients who had radical surgery. Nevertheless, they thought that conservative fertility-sparing surgery remains a reasonable option in the management of BOT.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In more advanced stages, where invasive implant is absent, lymph nodes are involved or rupture of the cyst has occurred, further studies have shown that chemotherapy has no effect on improving survival and reducing recurrence rate and/or improving the prognosis (39)(40)(41)(42).…”
Section: Postoperative Adjuvant Therapy (Chemotherapy Radiation)mentioning
confidence: 99%